2021
DOI: 10.3389/fphys.2021.609770
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Prognostic Risk Prediction Model of Oral Squamous Cell Carcinoma Based on Nine Survival-Associated Metabolic Genes

Abstract: The aim was to investigate the independent prognostic factors and construct a prognostic risk prediction model to facilitate the formulation of oral squamous cell carcinoma (OSCC) clinical treatment plan. We constructed a prognostic model using univariate COX, Lasso, and multivariate COX regression analysis and conducted statistical analysis. In this study, 195 randomly obtained sample sets were defined as training set, while 390 samples constituted validation set for testing. A prognostic model was constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…However, both studies lack validation from external cohorts. A nomogram incorporating a nine-metabolic-gene signature and several clinical characteristics performs well in discriminating patients with different outcomes with a C-index of 0.7, 19 which is comparable to the performance of the present model.…”
Section: F I G U R Esupporting
confidence: 65%
“…However, both studies lack validation from external cohorts. A nomogram incorporating a nine-metabolic-gene signature and several clinical characteristics performs well in discriminating patients with different outcomes with a C-index of 0.7, 19 which is comparable to the performance of the present model.…”
Section: F I G U R Esupporting
confidence: 65%
“…In recent years, studies on metabolic reprogramming of HNSCC during immune escape have shown that cancer cells can evolve and develop compensatory metabolic changes to escape death. In light of this, systemic manipulations to direct the tumor cell metabolic status to the normal cell status may reduce the malignancy (39)(40)(41). Studies have shown that metabolic therapy for certain metabolic processes provides an alternative for chemotherapy-resistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the upregulation of AGPAT4 in CRC cells most likely results in the decrease of T-cell activation and suppression of antitumor immunity. Microarray analysis studies of genes regulating lipid metabolism have further shown that AGPAT4 expression is upregulated in melanoma [ 98 ] and oral squamous cell carcinoma (OSCC) [ 99 ].…”
Section: The Role Of Agpats In Cancermentioning
confidence: 99%